2018
DOI: 10.1021/acs.jpcc.8b09189
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Behavior and Thermolysis Mechanisms of Ammonium Perchlorate under the Effects of Graphene Oxide-Doped Complexes of Triaminoguanidine

Abstract: Several transition metal complexes of triaminoguanidine (TAG) nitrate, TAG-Ni, TAG-Co, graphene oxide (GO)/TAG-Ni (GT-Ni), GO/TAG-Co (GT-Co), and GO/ TAG-Cu (GT-Cu) were prepared using GO as a stabilizer. It has been shown that these complexes are promising energetic catalysts for decomposition of ammonium perchlorate (AP), which was uniformly coated with the mentioned catalysts. The decomposition kinetic parameters and mechanisms of the complexes have been studied by means of differential scanning calorimetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 29 publications
5
32
1
Order By: Relevance
“…In addition G-T-Co, TAG-Co, and G-T-Cu 2 have stronger catalytic effects than nickel-based compounds, as they could make two-step gas releasing into one step. This conclusion is consistent with the thermal results from our previous research [17], which claimed that all TAG-M based composites could catalyze the first decomposition process of AP, and Co-based and Cu-based materials have stronger catalytic effects.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In addition G-T-Co, TAG-Co, and G-T-Cu 2 have stronger catalytic effects than nickel-based compounds, as they could make two-step gas releasing into one step. This conclusion is consistent with the thermal results from our previous research [17], which claimed that all TAG-M based composites could catalyze the first decomposition process of AP, and Co-based and Cu-based materials have stronger catalytic effects.…”
Section: Resultssupporting
confidence: 93%
“…Regarding G-T-Co/AP, the decomposition peak is smoother and the peak temperature increases by 10–20 °C with the addition of GO. It has been reported that G-T-Co can slightly increase the thermal stability of AP [17]. The results indicate that TAG-M complexes in the presence of GO can enhance thermal stability for AP, resulting in slower reaction rates at a higher temperature range.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The multi‐electron carriers had fast electrons transfer rate and could promote the generation of O 2 − [24,28–29] . As a result, the catalytic performance of n‐CuO has been greatly improved by adding the multi‐electron carrier [1,30–32] …”
Section: Introductionmentioning
confidence: 99%
“…Recently, the coordination of metal ions to energetic organic molecules has attracted much attention. transition metal (Cu, Co, and Ni) complexes of triaminoguanidine were shown to increase the thermal stability of ammonium perchlorate and efficiently promote its decomposition [22][23][24]. Previously, Co/Cu/Ni/Fe salts of 3nitro-1,2,4-triazol-5-one (NTO) were developed from NTO, which improved the burning rate by about 80 % and decreased the pressure index to 0.18 (2-9 MPa) [25].…”
Section: Introductionmentioning
confidence: 99%